2009
DOI: 10.4161/cc.8.4.7731
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of intracranial glioma growth by endometrial regenerative cells

Abstract: Animal studies have demonstrated that selective tropism of mesenchymal stem cells (MSC) for glioma may be used as a means of selective delivery of cytotoxic payloads. Endometrial Regenerative Cells (ERC) are a population of mesenchymal-like cells which possesse pluripotent differentiation capacity and is characterized by unique surface markers and growth factor production. In this study we sought to determine whether unmanipulated ERC would alter the growth of glioma using the aggressive C6/LacZ7 (C6) into Spr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 45 publications
0
31
0
1
Order By: Relevance
“…Moreover, to assess whether MenSCs modulate tumor growth, a rat glioma model was used. The injected cells showed a substantial inhibition of the tumor growth when compared to the control group (49). …”
Section: Safety Concerns and Clinical Applicationsmentioning
confidence: 88%
“…Moreover, to assess whether MenSCs modulate tumor growth, a rat glioma model was used. The injected cells showed a substantial inhibition of the tumor growth when compared to the control group (49). …”
Section: Safety Concerns and Clinical Applicationsmentioning
confidence: 88%
“…In comparison to other stem cell types, they have shown some advantages that make them a considerable source in cell therapy. Some advantages are immunosuppressive potential [15] and higher clonogenisty (1.25 %) in comparison with umbilical cord blood stem cells (UCBSCs), and no shown development of teratoma unlike embryonic stem cells [16,17]. Earlier studies have demonstrated their differentiation ability toward neuron-like cells [18][19][20] and oligodendrocyte [21].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, NSCs, MSCs, endothelial, hematopoietic, skinderived, and endometrial precursor cells have been utilized as migratory cellular vectors to tumors. [18][19][20][21][22][23] The first evidence of the tropism of MSCs to gliomas was demonstrated by implantation of rat MSCs into rats bearing syngeneic gliomas. 20 Intracranially implanted MSCs were found to migrate to and disperse throughout the tumor mass.…”
Section: Mscsmentioning
confidence: 99%